"Attitude of education stakeholders towards maintenance of school resources: an educational psychologists perspective , " (2013)
This paper examined the relevance of maintenance of school resources in the achievement of educational goals and objectives. It equally highlights the quantity and quality of the school resources within the reach of schools. Attention was highly paid on non-challant attitude of some education stakeholders (parents, teachers, government and even the students who are direct beneficiary of all educational programmes). Most of them holds, carelessly, some major school resources such as turning out school premises to political meetings and other social engagement which reduces the quality and quantity of materials available in the school setting there after some recommendations were made which includes among others; government should encourage education stakeholders to maintain school resources adequately to avoid a waste. School resources must be provided and maintained correctly by education stakeholders. Political meetings and other social meetings in school should be stopped. The general public should be sensitize to the need for maintenance culture in the school and the society at large etc.